2020
DOI: 10.1007/s42600-019-00036-9
|View full text |Cite
|
Sign up to set email alerts
|

Applicable features of electroencephalogram for ADHD diagnosis

Abstract: Purpose Attention-deficit/hyperactivity disorder (ADHD) is a neuro-developmental and psychiatric disorder, which affects 11% of children around the world. Several linear and nonlinear biomarkers from electroencephalogram (EEG) signals have been proposed for diagnosis of ADHD to date. However, the determination of which type of analysis gives us the best feature and biomarker to diagnose ADHD is still controversial. In this study, we aimed to evaluate and compare several categories of features, extracted from E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…Statistical analysis showed that 13.15, 13.68, 14.47, 14.03, and 34.73% of the extracted features were significant in morphology, time, frequency, time frequency, and nonlinear domain ( P < 0.05). The maximum AUC values of five categories such as morphological, temporal, frequency, time frequency, and nonlinear feature are 0.870, 0.796, 0.824, 0.806, and 0.899 [ 8 ]. Wavelet packet decomposition reconstruction of affective EEG signals and the ß rhythm was used for affective state recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis showed that 13.15, 13.68, 14.47, 14.03, and 34.73% of the extracted features were significant in morphology, time, frequency, time frequency, and nonlinear domain ( P < 0.05). The maximum AUC values of five categories such as morphological, temporal, frequency, time frequency, and nonlinear feature are 0.870, 0.796, 0.824, 0.806, and 0.899 [ 8 ]. Wavelet packet decomposition reconstruction of affective EEG signals and the ß rhythm was used for affective state recognition.…”
Section: Introductionmentioning
confidence: 99%
“…This can be supported by a more focus on establishing utility through the active application of computational appro-aches in clinical trials. Combining theory- and data-driven approaches can be an appropriate way [ 14 , 75 - 79 ]. Combining theory- and data-driven approaches can be very helpful from an applied point of view [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Larger tests should be performed, not only to increase the confidence in method and allow meta parameter optimization, but also to test the performances of other nonlinear features in the MSWSA method. The selection of the nonlinear feature should include those commonly studied for ADHD [56][57][58], ADD [59] and ANX [60]. Also, only the MSWSA was used for classification to show that the featured contained information useful for classification purpose.…”
Section: Discussionmentioning
confidence: 99%